1992
DOI: 10.12968/jowc.1992.1.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a calcium alginate dressing for venous ulcers of the leg

Abstract: A small study of Tegagel calcium alginate dressings is described, with a discussion of the methodology employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Thus, the final data set included 19 RCTs evaluating 39 unique treatments (Table 69). 227,231,[282][283][284][285][286][287][288][289][290][291][292][293][294][295][296][297][298] The evidence in the final data set was organised in the network, shown in Figure 16.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the final data set included 19 RCTs evaluating 39 unique treatments (Table 69). 227,231,[282][283][284][285][286][287][288][289][290][291][292][293][294][295][296][297][298] The evidence in the final data set was organised in the network, shown in Figure 16.…”
Section: Resultsmentioning
confidence: 99%
“…The increased weighting of indirect compared with direct data occurred here because the effect estimate derived from the study populating the alginate vs. foam comparison 294 was more precise than the estimate derived from the study populating the alginate vs. basic wound contact comparison. 287 The mixed-treatment estimate for alginate versus hydrocolloid was also mainly informed by direct evidence from other pairwise comparisons: the alginate versus foam and foam versus hydrocolloid comparisons.…”
Section: Contributions Of Direct Evidence (Non-silver Dressings)mentioning
confidence: 99%
“…From those included, 22 studies 30–51 evaluated the use of modern vs. conventional dressings, and nine 52–60 were comparative studies of different modern dressings. Twenty‐six studies 30–48,52–58 corresponded to ulcers of venous origin and five 49–51,59 , 60 to leg ulcers whose etiology was not clearly identified. No study that exclusively targeted arterial ulcers and met the inclusion criteria was identified.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3, no differences were observed in the outcome, “healing,” in any of the studies that compared: an alginate against a conventional dressing 41 or zinc‐impregnated gauze; 46 collagen against a nonadherent dressing; 47 or activated carbon against paraffin‐soaked gauze 48…”
Section: Resultsmentioning
confidence: 99%
“…Five RCTs (295 participants) were included (Armstrong 1997;Harding 2001;Límová 2003;Mo att 1992;Smith 1994). One was undertaken in the USA (Límová 2003), one in France and the UK (Armstrong 1997), and the remaining three solely in the UK (Harding 2001;Mo att 1992;Smith 1994). Three were multicentre RCTs (Armstrong 1997;Harding 2001;Límová 2003).…”
Section: Included Studiesmentioning
confidence: 99%